Correlation Between Motivation and Ability to Perform Work of the Employees at Department of Public Works and Transport, Luang Prabang Province - THAVYCHAY, Saykeo; Duangvilaykeo , Thipphavanh; Sisavanh , Orathai (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study examined to 1) the capacity levels and work motivation of employees at the Department of Public Works and Transport of Luang Prabang Province, and 2) analyzed the correlation between employee motivation and work performance ability. The sample size of 140 employees. Data were collected through questionnaires and analyzed using SPSS version 25 to generate descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics using Pearson's correlation coefficient. The findings indicated that: The capacity levels and work motivation of employees at the Department of Public Works and Transport of Luang Prabang Province such as 1) the employee motivation at a good level ( 4.10, SD=0.51), employees at the Department of Public Works and Transport of Luang Prabang Province rated the overall importance of hygiene factors at a good level ( 3.96, SD=0.53), and 2) the employee performance capability at a good level ( 4.11, SD=0.54. When examining individual components, employees rated knowledge and ability to perform, skills for their own work and individual characteristics. Correlation analysis revealed statistically significant strong positive relationships between all motivation factors and work performance ability, with Pearson correlation coefficients ranging from r = 0.46 to r = 0.80 (p < 0.01). These findings suggest that both intrinsic and extrinsic motivational factors significantly influence employee performance capacity in public sector organizations.